Randomized, double‐blind, controlled study of glycerol phenylbutyrate in hepatic encephalopathy. Issue 3 (March 2014) - Rockey, Don C.; Vierling, John M.; Mantry, Parvez; Ghabril, Marwan; Brown, Robert S.; Alexeeva, Olga; Zupanets, Igor A.; Grinevich, Vladimir; Baranovsky, Andrey; Dudar, Larysa; Fadieienko, Galyna; Kharchenko, Nataliya; et al.
<x xml:space="preserve">Abstract</x> Glycerol phenylbutyrate (GPB) lowers ammonia by providing an alternate pathway to urea for waste nitrogen excretion in the form of phenylacetyl glutamine, which is excreted in urine. This randomized, double‐blind, placebo‐controlled phase II trial enrolled 178 patients with cirrhosis, including 59 already taking rifaximin, who had experienced two or more hepatic encephalopathy (HE) events in the previous 6 months. The primary endpoint was the proportion of patients with HE events. Other endpoints included the time to first event, total number of events, HE hospitalizations, symptomatic days, and safety. GPB, at 6 mL orally twice‐daily, significantly reduced the proportion of patients who experienced an HE event (21% versus 36%; P = 0.02), time to first event (hazard ratio [HR] = 0.56; P < 0.05), as well as total events (35 versus 57; P = 0.04), and was associated with fewer HE hospitalizations (13 versus 25; P = 0.06). Among patients not on rifaximin at enrollment, GPB reduced the proportion of patients with an HE event (10% versus 32%; P < 0.01), time to first event (HR = 0.29; P < 0.01), and total events (7 versus 31; P < 0.01). Plasma ammonia was significantly lower in patients on GPB and correlated with HE events when measured either at baseline or during the study. A similar proportion of patients in the GPB (79%) and placebo groups (76%) experienced adverse events. Conclusion: GPB reduced HE events as well as ammonia in patients with cirrhosis and HE and its safety profile was similar to placebo. The findings implicate ammonia in the pathogenesis of HE and suggest that GPB has therapeutic potential in this population. (Clinicaltrials.gov, NCT00999167). (Hepatology 2014;59:1073‐1083)